Overactivation of the NF‐κB pathway impairs molar enamel formation. (9th July 2020) - Yamada, Akane; Kawasaki, Maiko; Miake, Yasuo; Yamada, Yurie; Blackburn, James; Kawasaki, Katsushige; Trakanant, Supaluk; Nagai, Takahiro; Nihara, Jun; Kudo, Takehisa; Meguro, Fumiya; Schmidt‐Ullrich, Ruth; et al.
Abstract: Objective: Hypohidrotic ectodermal dysplasia (HED) is a hereditary disorder characterized by abnormal structures and functions of the ectoderm‐derived organs, including teeth. HED patients exhibit a variety of dental symptoms, such as hypodontia. Although disruption of the EDA/EDAR/EDARADD/NF‐κB pathway is known to be responsible for HED, it remains unclear whether this pathway is involved in the process of enamel formation. Experimental subjects and methods: To address this question, we examined the mice overexpressing Ikkβ (an essential component required for the activation of NF‐κB pathway) under the keratin 5 promoter ( K5‐Ikkβ ). Results: Upregulation of the NF‐κB pathway was confirmed in the ameloblasts of K5‐Ikkβ mice. Premature abrasion was observed in the molars of K5‐Ikkβ mice, which was accompanied by less mineralized enamel. However, no significant changes were observed in the enamel thickness and the pattern of enamel rods in K5‐Ikkβ mice. Klk4 expression was significantly upregulated in the ameloblasts of K5‐Ikkβ mice at the maturation stage, and the expression of its substrate, amelogenin, was remarkably reduced. This suggests that abnormal enamel observed in K5‐Ikkβ mice was likely due to the compromised degradation of enamel protein at the maturation stage. Conclusion: Therefore, we could conclude that the overactivation of the NF‐κB pathway impairs the process of amelogenesis.